Dynamics of Social and Religious Interaction in Multicultural Society: A Case Study in Medan City - II, Harianto; Sutikno, Sutikno; Kartolo, Rahmat (LPPM Universitas PGRI Sumatera Barat, 2023)
This qualitative study explores social and religious interactions in Medan, Indonesia. Medan has many ethnic and religious groups. This diversity makes it a great place to see how communities live together and handle conflicts. Researchers collected data through interviews with community leaders, religious figures, and residents. They also did participant observation and analyzed relevant documents. The findings indicate that interactions among different groups are mostly positive. People show mutual respect and engage in shared activities. Interfaith talks and joint efforts, usually guided by religious leaders and local governments, improve understanding and tolerance. Yet, some problems persist. These are stereotypes, competition for resources, and the political manipulation of identities. The study highlights the importance of good communication, community efforts, and inclusive policies. These are key to building social cohesion. Medan's diverse culture creates opportunities for positive connections. Still, we must keep working to face challenges and prevent conflicts. This research adds to the discussion on managing diversity and fostering peaceful coexistence in urban Indonesia.